Multilingualism, Technology, and Religious Moderation in Indonesian Islamic Boarding Schools - Subair, Muh.; Syamsurijal, Syamsurijal; Rismawidiawati, Rismawidiawati; Idham, Idham; Muslim, Abu; Nur, Muhammad (Universitas Negeri Makassar, 2024)
Communities that can speak more than one language as a daily habit are not only happening in the present era but have long existed in the pesantren environment. However, multilingualism in pesantren is often only seen as a capacity enhancement of the santri's knowledge. On the other hand, the multilingual ability of the Santri is an asset in forming an attitude of religious moderation. This article then presents the results of qualitative research using the concept of additive multilingualism which focuses on pesantren students in Indonesia. Through observations, interviews, and literature review, this research can describe the reality of multilingualism in pesantren and its impact on the religious attitudes of its santri. It turns out that the religious moderation attitude of the students is closely related to the multilingual learning process in pesantren that takes place with technological restrictions. The application of additive multilingualism is aligned with the pillars of religious moderation in four ways. First, respect for locality is reflected in the Santri's habit of using local languages. Second, multilingualism is an expression of anti-violence, this is reflected in Santri's acceptance of linguistic and ethnic diversity as a brotherhood base. This is what manifests in the Third pillar by making santri a tolerant community as a result of learning from the reality of ethnic and linguistic diversity in their environment. Fourth, the introduction of santri to foreign languages is directed to reaffirm their national commitment through the use of foreign languages in flag ceremonies. The limitation of technology in multilingual learning is also intended to keep students from the bad influence of technology and to maintain the discipline of students in maintaining a pesantren culture that is friendly to locality and sensitive to the times